Program Rupa Reka UMKM Dalam Memanfaatkan Platform Digital Untuk Pemasaran Dan Penjualan Produk Gula Kawung Desa Sadapaingan Kabupaten Ciamis - Syuhada, Otong; Dewi, Rani; Pribadi , Riky (Universitas Majalengka, 2023)
The implementation of Thematic Community Service Program (KKN-T) in Sadapaingan Village is directed to develop local potential while addressing priority village problems. This program is focused on the MSME sector. By involving students, village government, and the community, KKN-T is expected to create sustainable solutions and become a model for village development that can be replicated in other areas. MSMEs have not yet developed and local economic potential has not been optimized Digital marketing training, creation of Google Maps & QRIS accounts, as well as branding and digital marketing education for MSME actors. The objectives to be achieved through the KKN-T program in Sadapaingan Village are: Digitalization and Empowerment of MSMEs Through; 1. Increasing the capacity of MSME actors in Sadapaingan Village in utilizing digital platforms for product marketing and sales; 2. Expanding the reach of the MSME market, increasing product visibility, and encouraging village economic growth. The RUPA REKA UMKM program provides mentoring to local MSMEs, namely Gula Kawung Ma Didin and Ma Nonoh on July 21, 2022, and Rengginang Pak Ujang on July 22, 2022. UNMA Community Service Program (KKN-T) students assisted these MSMEs in creating product logos, banners, signposts for their production locations, and listing their locations on Google Maps. The goal was to increase sales volume and enhance business visibility.